Pengaruh Pendapatan dan Ukuran Perusahaan Terhadap Kinerja Keuangan pada Asuransi Syariah di Indonesia Tahun 2019-2022 - Syamsul Arifin; Subandi Subandi; Didik Kusno Aji; Finny Ligery (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of revenue and company size on financial performance in Islamic insurance companies in Indonesia registered with the Financial Services Authority (OJK) during the 2019–2022 period. This study combines the analysis of two main factors, namely revenue and company size in the context of the Islamic insurance industry specifically. Islamic insurance companies registered with the Financial Services Authority (OJK) for the 2019–2022 period. Data were analyzed using multiple linear regression. Based on the results of hypothesis testing, it is known that: (1) Revenue does not have a significant effect on financial performance (p = 0.051 > α = 0.05); (2) company size has a significant effect on financial performance (p = 0.000 < α = 0.05); and (3) Revenue and company size simultaneously have a significant effect on financial performance (p = 0.000 < α = 0.05). The implications of this study indicate that companies need to strengthen their asset structure to improve efficiency and profitability